If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6a + -7 = 2a + 1 Reorder the terms: -7 + 6a = 2a + 1 Reorder the terms: -7 + 6a = 1 + 2a Solving -7 + 6a = 1 + 2a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2a' to each side of the equation. -7 + 6a + -2a = 1 + 2a + -2a Combine like terms: 6a + -2a = 4a -7 + 4a = 1 + 2a + -2a Combine like terms: 2a + -2a = 0 -7 + 4a = 1 + 0 -7 + 4a = 1 Add '7' to each side of the equation. -7 + 7 + 4a = 1 + 7 Combine like terms: -7 + 7 = 0 0 + 4a = 1 + 7 4a = 1 + 7 Combine like terms: 1 + 7 = 8 4a = 8 Divide each side by '4'. a = 2 Simplifying a = 2
| 2(3u-6)=12 | | X=9+6i | | 4=12+4z | | -5-y=12 | | 2(1[3u-6]1)=12 | | -5x+4(-1)=-24 | | -2y-8=1-4y | | 3x-8(1/x)=10 | | 2/3(m)=16 | | 2(ps+3)=6(3s+1) | | g=f-360/15 | | 2x-3,5(x-4)=6 | | 5/8X6 | | 6(5x+4)+6x-2=5(7x+2) | | 7x-14=5x+24 | | 2x-2-x-1=x-1+x+1 | | x^2+36=85 | | 5a^2+38a+21=0 | | 2x-2x+1=2x-7x-1 | | -3x-8(-5x+1)=20 | | -5(-3y+1)+4y=-24 | | -5(3y+1)+4y=-24 | | 4z+12=4 | | -3(-5x+19)-8y=20 | | 81x^2/121 | | 3/4(x-2)=x/6-1 | | x=1/4y-8 | | 16t^2-64t-12=72 | | 8+3x=29+x | | 4x+36y=-16 | | -(z/3)-(3/4) | | 3a+6b+2a= |